IT Innovation for Adaptability and Competitiveness - Fitzgerald, Brian.; Wynn, Eleanor. (IFIP International Federation for Information Processing,, 2004)
IT Innovation for Adaptability and Competitiveness addresses the topic of IT innovations that can further an organization's ability to adapt and be competitive. Thus we address the problem at an earlier starting point, that is, the emergence of something innovative in an organization, applied to that organization, and its process of being diffused and accepted internally. Topics covered in the book include: -The role of IT in organizational innovation, -Innovating systems development & process, -Assessing innovation drivers, -Innovation adoption, -New environments, new innovation practices. This volume contains the edited proceedings of the Seventh Working Conference on IT Innovation for Adaptability and Competitiveness, which was sponsored by the International Federation for Information Processing (IFIP) Working Group 8.6 and held at Intel Corporation, Leixlip, Ireland in May-June 2004.